The Urgency of Halal Tourism Regulations Under Law No. 10 of 2009 on Tourism: Toward a Muslim-Friendly Tourism Ecosystem in Indonesia - Rika Puspita Sari; Riza Puspita Sari (RESPONSIVE LAW JOURNAL, 2026)
This study aims to analyze the urgency of regulating halal tourism within the framework of Law No. 10 of 2009 concerning Tourism to foster a Muslim-friendly tourism ecosystem in Indonesia. It also seeks to analyze the obstacles to and solutions for the implementation of halal tourism in the country. The absence of specific regulations governing halal tourism in Indonesia has created a legal vacuum. A qualitative research method with a normative-juridical approach was employed. The study concludes that specific regulations for halal tourism are essential, as there is currently no dedicated legal protection for tourists or business operators in this sector; consequently, despite the promising growth of halal tourism in Indonesia, the lack of appropriate and adequate regulation leaves the sector vulnerable. Identified obstacles include a lack of public understanding regarding halal tourism, insufficient infrastructure to meet the needs of Muslim tourists, a large number of Micro, Small, and Medium Enterprises (MSMEs) lacking halal certification, and the absence of specific halal tourism regulations. Proposed solutions include the government and relevant institutions conducting large-scale, sustained public awareness campaigns on the concept of halal tourism; developing infrastructure and facilities that support halal tourism; promoting free halal certification programs; and enacting specific regulations for halal tourism in Indonesia.